The mandarese gastronomy: Preference and opportunities for food diversification on the dining table of young generations - Kasmiati, Kasmiati; Karim, Ikawati; Farid Karim, Faradilah (Anjoro: International Journal of Agriculture and Business, 2022)
The circulation of global food, especially fast food like sausages, nuggets, fried chicken such as KFC, and other instant food, has been circulating into rural areas. Many estimated younger generation's preferences would change under these conditions. Because of that, we were conducted research in the Tinambung, Polewali Mandar District, West Sulawesi Province, from May to August 2021 to understand the young preferences for food. The research found that the Millennial, Z, and Alpha generations of Mandarese still have a good preference for their local gastronomy. The types of the Mandarese food on this study are Baupiapi, Jepa, Bubur Tarreang, Loka Anjoroi, and Binte. Those are made from local raw materials such as cassava, banana, coconut, fish, millet, and corn. These agricultural and local raw materials can be the basis for developing more diverse food for the daily consumption of the youth. The young generation's preferences are essential because their population is enormous. It means their food preference will affect the food system. It can also be a factor in determining a future food diversification policy and self-sufficiency of the Mandarese. Currently, the highest preference of the young generation in Polewali Mandar still tends to like and choose Mandar gastronomy compared with global foods. It shows that local foods are still in line with the youth's preferences but need to develop as an essential part of their daily consumption. Their preferences for local gastronomy are still facing challenges; it will be more diverse or even the other way around because of the hegemony of the global food trend.